ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN LOOSE PART PADA TK NEGERI MATAWAI AMAHU - Radja, Petrus Logo; Saefatu, Irony Damianus; Seran, Engelbertus; Giri, Raijes Fares (Jurnal Dedikasi Pendidikan, 2025)
This is a new author guidelines and article template of Jurnal Dedikasi Pendidikan. Article should be Children often perceive activities like playing, singing, and listening to stories as simple, monotonous, and meaningless in early childhood education. Teachers can make learning meaningful by using enjoyable learning media, one of which is Loose Part media. Loose Parts is a medium that is currently popular among teachers, but sometimes teachers do not fully understand the characteristics, types, benefits, usage or application, challenges or obstacles faced, and solutions to the challenges or obstacles encountered when using Loose Parts. The research shows that teachers at TK Negeri Matawai Amahu have used Loose Parts in their lessons by using what they had on hand and thinking about things like the child's age, the benefits, the goals, the right way to use or apply the Loose Parts, and how the child is developing. The challenges encountered by teachers during the use of Loose Parts were more about how to select and prepare Loose Parts that meet the children's needs. The teachers can effectively address the challenges encountered in using Loose Parts. Based on the research results, it can be concluded that the teachers at TK Negeri Matawai Amahu have a very good understanding of the use of Loose Parts